2007
DOI: 10.1002/ange.200603471
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Complex of Cytochrome c with a Polyanionic β‐Cyclodextrin

Abstract: Eine Dreiergruppe: Ein anionisches Cyclodextrin bindet elektrostatisch an kationisches Cytochrom c (K=2.3×104 M−1, ΔH=9.3 kJ mol−1, ΔS=115 J mol−1 K−1). Dabei deckt das Cyclodextrin die Hämintaschen von etwa zwei Drittel der cyt c‐Moleküle ab. Dieser Assoziationskomplex bindet weiter an ein nichtionisches Porphyrin zu einem ternären Komplex, in dem die statische Fluoreszenz von Porphyrin durch cyt c gelöscht wird.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The calorimetric titration curves for the cyt c/CDM‐β‐CD system were well‐fitted to the equation for 1:1 complex formation. As found previously,14 the complexation is endothermic and is driven by the entropy term, which suggests the occurrence of extended dehydration from both cyt c and CDM‐β‐CD upon association. The plot of Δ H 0 versus T showed poor linearity in this system (see Supporting Information).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The calorimetric titration curves for the cyt c/CDM‐β‐CD system were well‐fitted to the equation for 1:1 complex formation. As found previously,14 the complexation is endothermic and is driven by the entropy term, which suggests the occurrence of extended dehydration from both cyt c and CDM‐β‐CD upon association. The plot of Δ H 0 versus T showed poor linearity in this system (see Supporting Information).…”
Section: Resultssupporting
confidence: 78%
“…We used heptakis(6‐carboxymethyl‐2,3‐di‐ O ‐methyl)‐β‐CD (CDM‐β‐CD) in the dissociated form as the polyanionic CD. Our previous study showed that CDM‐β‐CD is bound to horse heart cytochrome c (cyt c; pI 10.4) in 0.01 M aqueous NaCl at pH 7.0 through Coulomb interactions 14. Such a simple system would be appropriate for studying Δ C p 0 in protein–ligand complexation through Coulomb interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Complex formation through electrostatic interaction in aqueous solution is usually driven by a favorable entropy term owing to dehydration from both host and guest. [15] These findings suggest that electrostatic interaction is not the sole binding force for the P1-V3 Ba-L and Fe III P1-V3 Ba-L systems. Although coordination of imidazole to iron porphyrins is an enthalpically favorable process, [16] the DH 0 (À62 kJ mol À1 ) for the Fe III P1-V3 Ba-L system was almost the same as that (À63 kJ mol À1 ) for the P1-V3 Ba-L system.…”
Section: Thermodynamic Parametersmentioning
confidence: 92%
“…Complexation of multivalent organic ions with oppositely charged ligands in aqueous solution commonly shows positive entropy changes. [15] Extended dehydration from both ions upon association is the origin of the positive DS 0 . As the complexation of both the anionic porphyrins with V3 IIIB having a net charge of +8 is still enthalpically dominated, van der Waals interaction also plays an important role.…”
Section: Thermodynamic Parametersmentioning
confidence: 99%